The 2011 proposed revisions to the code of corporate governance, 2005 : impacts and implications - Le, Nhi Nuong (2012)
This study examines the readiness level of Singapore's top 50 SGX and Catalist listed companies to adopt the revised Code of Corporate Governance proposed by the Singapore Corporate Governance Council on the 14th of June 2011. It also explored the key areas where there might be implementation issues such as the remuneration disclosure and the tightening of the definition of independent director. Lastly, the study gave insights into the legal ramifications of directors and top executives for certifying the financial records' accuracy and giving assurances with regards to the adequacy of the company's internal controls and risk management. Legal ramifications were discussed based on the implementation of the Clawback provision and duty of care between directors and shareholders, when the plaintiff if the company and shareholders respectively.